Optimization of multi-channel ground-penetrating radar for quantifying field-scale soil water dynamics - Pan, Xicai; Wollschläger, Ute; Gerhards, Holger; Roth, Kurt (Journal of applied geophysics, 2012)
Continuous multi-offset surveys conducted with multi-channel ground-penetrating radar (GPR) systems have already shown their potential for a fast and high-resolution mapping of near-surface soil architecture and volumetric soil water content. Here, we study the accuracy of an 8-channel setup as a function of antenna separation, reflector depth and dielectric permittivity. This is done by Monte Carlo simulations that add noise to the components of the measuring process. We find that adapting the antenna setup to the particular situation is mandatory for an optimal accuracy. In the second step, we demonstrate the applicability and accuracy of our approach with a time-series of real data from a site with two pronounced reflectors. We find that the measured radargrams are highly reproducible and allow to determine reflector depths with an accuracy of about 0.1m and soil relative dielectric permittivity with an accuracy of about 0.5. With this we quantify the effective field-scale dynamics of soil water for the layers between the ground-surface and the reflectors.